Effect of Routes of Infection on the Pathology and Pathogenesis of Velogenic Newcastle Disease Virus in Cockerel Chickens - Ezema, Wilfred Sunday; Eze, Chekwube Paul; Ezema, Anastasia Nebechi; Ogbonna, Innocent Okonkwo; Okoye, John O. Arinze (International Journal of Poultry Science, 2025)
Objective: This study was conducted to investigate the effects of routes of infection on pathogenesis of Newcastle Disease Virus (NDV) infection. Materials and Methods: A total of two hundred and eighty day-old chicks were used in this study. At six weeks of age, the birds were randomly divided into five groups (A, B, C, D and E) of 60 birds per group except group D with 40 birds. The inoculum of Velogenic Newcastle Disease Virus (VNDV) Kudu113 strain, acquired from NVRI Vom was diluted with PBS to 104.36 per milliliter (ELD50). Each bird from groups A, B and C received 0.2mL of the inoculum, orally, intramuscularly (IM) and intratracheally (IT) respectively. In group D, 10 birds were tagged and introduced into each of the groups A, B, C and E, to be challenged through contact. The clinical signs, body weight and PM lesions were recorded; the hematology, HI titre was determined. The data obtained were subjected to one-way analysis of variance (ANOVA). Results: The birds infected through IM came down with the clinical signs of NDV such that 25% presented with depression and greenish diarrhea by day 2 PI but reached 100% mortality by day 6 PI. The birds infected through IT also came down with the infection on day 2 PI with 5% depression, greenish diarrhea and 100% mortality by day 6 PI. Birds infected through oral and contact routes had depression rate of 85 and 66.7%, respectively. Orally infected birds had 100% mortality by day 9 PI while those infected through contact had 100% mortality by day 11 PI. The lesions of NDV persisted for 5 to 6 days in the birds infected via IM and IT. But those infected by oral and contact routes had lesion (severe atrophy of the thymus, bursa, proventricular hemorrhages and intestinal ulcers) which persisted till day 10 PI. Conclusion: The result of this study has shown that severity and duration of Newcastle disease in chickens depend on the route of infection.